Dementia in Clinical Practice: A Neurological Perspective Studies in the Dementia Clinic - Larner, A.J (Springer London : Imprint: Springer, 2012)
Dementia in Clinical Practice: A Neurological Perspective addresses neurological contributions to the diagnosis and management of dementia through a longitudinal examination of the work undertaken in dedicated neurological dementia clinics. This concise, pragmatic handbook covers: The use of cognitive screening instruments and their diagnostic utility. The use of non-cognitive (functional, behavioural, neurovegetative) screening instruments and their diagnostic utility. The use of other diagnostic investigations: neuroimaging, neurophysiology, neuropathology. The diagnostic mix in terms of both neuropsychological syndromes and neurological diagnoses. The use of conventional treatments for dementia. The impact of national directives (e.g. NICE, National Dementia Strategy) on day-to-day clinical practice. Dementia in Clinical Practice: A Neurological Perspective is an illustrated, practical resource for medical professionals involved in the assessment and management of dementia patients. It is of particular benefit to neurologists, psychiatrists, geriatricians, primary care practitioners and those working in the fields of neuropsychology, psychology, occupational therapy, speech and language therapy and nursing.